Plasma instabilities of a charge breeder ECRIS. (15th September 2017) - Tarvainen, O; Angot, J; Izotov, I; Skalyga, V; Koivisto, H; Thuillier, T; Kalvas, T; Lamy, T
Abstract: Experimental observation of plasma instabilities in a charge breeder electron cyclotron resonance ion source (CB-ECRIS) is reported. It is demonstrated that the injection of 133 Cs + or 85 Rb + ion beam into the oxygen discharge of the CB-ECRIS can trigger electron cyclotron instabilities, which restricts the parameter space available for the optimization of the charge breeding efficiency. It is concluded that the transition from a stable to unstable plasma regime is caused by gradual accumulation and ionization of Cs/Rb and simultaneous change of the discharge parameters in 10–100 ms time scale, not by a prompt interaction between the incident ion beam and the ECRIS plasma. The instabilities lead to loss of ion confinement, which results in the sputtering of the surfaces in contact with the plasma, followed by up to an order of magnitude increase of impurity currents in the extracted n + ion beam.